The Effect Of Cashback Programs, Bonus Packs And Diapers Price Discounts On Purchasing Interest At E-Commerce Shopee - Herliani, Mia; Alim, Syahrul (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
In order to increase sales and attract consumers, e-commerce carries out large-scale promotions every month. Usually, this promotion falls on beautiful dates, one of which is the promotion 11.11, 12.12 and other beautiful dates. Of course, this promotion not only provides benefits for e-commerce itself, consumers can also shop economically by getting cheap prices. And of course, sellers because they can increase product sales. This research is quantitative and uses SPSS analysis tools. This research aims to disseminate the impact of e-commerce promotions on interest in buying diapers. There were 100 respondents in this study, namely consumers of the Arfan milk shop. From the data processing that has been carried out, it is known that Purchasing Interest partially has a positive and significant effect on Purchase interest in Toko susu Arfan